Identification of a permanent reservoir of bromine in Arctic snow in the form of bromate (BrO3-). - Stefano Frassati; Elena Barbaro; Giulio Cozzi; Clara Turetta; Federico Scoto; Alfonso Saiz-Lopez; Kitae Kim; Ward van Pelt; Carlo Barbante; Andrea Spolaor (International Conference on the Physics and Chemistry of Ice (PCI-2023), 2023)
Bromine (Br) and iodine (I) are chemical species that play central roles in polar atmospheric chemistry, ozone depletion, and cloud condensation nuclei formation and the natural sources to the atmosphere is the ocean1. In particular, bromine undergoes a series of autocatalytic reactions that lead to sunlight-induced ozone depletion, these reactions are known as “bromine explosion”2. This catalytic cycle occurs at the air-snow interface, but currently, photochemical reactions are only included in the gas phase and possible photo-oxidation of bromine in snow is not addressed. In this study, an analytical method for the speciation of Br and I was developed by ion chromatography system (IC) coupled with inductively coupled plasma sector field mass spectrometer (ICP-SFMS). Thanks to this instrumental set-up we were able to achieve detection limit (LOD) of 0.3 pg g-1 for I-, 1.13 pg g-1 for IO3 -, 3.6 pg g-1 for Br-, and 2.1 pg g-1 for BrO3 -, respectively. This analytical method has been used to analyze snow samples from Holtedahlfonna glacier (HDF, Svalbard Islands) collected in interval of 10 cm. For the first time, through fine-tuning of IC/ICP-SFMS technique, it was possible to detect bromate (BrO3 -) in Artic snow at pg g-1 level. The most interesting result is that the concentration of BrO3 - remains almost constant in the deepest samples corresponding to the polar night period, but there is a significant increase in the layers exposed to sunlight. This mean that oxidation processes of bromine could occur into the snowpack producing, although in low percentage, a reservoir of inactive bromate species.